Funk & Wagnalls standard dictionary of folklore, mythology and legend Fried, associate editor. - Leach, Maria (New York Funk & Wagnalls, 1949)
Contains over 4000 entries about folk stories and songs, gods, heroes, fairies and demons, angels and devils, ogres,guardian spirits, witches, vampires and zombies of many cultures
v. 1. A-I -- v. 2. J-Z
Also issued online
Keywords: Folklore -- Dictionaries; Legends -- Dictionaries; Mythology -- Dictionaries; Folklore -- Dictionary -- English; Folklore -- Dictionaries